Antioxidant, antimicrobial activity and in-vitro cytotoxicity screening study of pili nut oil - Zarinah, Zakaria; A.G., Maaruf; R., Nazaruddin (2014)
Some vegetable oils contain natural antioxidants such as beta carotene and vitamin E namely alpha tocopherol. The objective of this study was to screening the value of α-tocopherol, β-carotene, antioxidant capacity, antimicrobial activity and toxicological properties of roasted pili nut oil (RPNO) and unroasted pili nut oil (UPNO). The result showed that RPNO contained higher amount of vitamin E and less amount of beta carotene compared to UPNO. RPNO and UPNO scavenged DPPH radicals by 24.66% and 9.52% at concentration of 140 µg/ml. The total phenolic compound (TPC) in UPNO and RPNO were about 19.96 ± 0.52 mg/kg and 12.43 ± 0.69 mg/kg respectively. It was observed that bacteria species exhibited different sensitivities towards RPNO, UPNO, Gentamycin, Ampicillin and Chloramphenicol. Bacillus cereus 14570 was the most sensitive bacterium and all strains of Staphylococcus aureus tested were resistant against both samples RPNO and UPNO. An in vitro toxicological study based on the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) cytotoxicity assay was also performed. In vitro cytotoxicity indicated that both RPNO and UPNO had no effect against HeLa (cervical cancer cell), MCF-7 (breast cancer cell) and HT-29 (human colon adenocarcinoma cell) cell lines tested.